Adding one more to the list: A new species of Eniochobothrium (Cestoda: Lecanicephalidea) from the Oman cownose ray in South Africa. (December 2022) - Oosthuizen, Geraldine; Naidoo, Kristina; Smit, Nico J.; Schaeffner, Bjoern C.
Abstract: A new species of Eniochobothrium Shipley and Hornell, 1906 was recovered from the Oman cownose ray ( Rhinoptera jayakari Boulenger) from the body of water off the south-eastern coastline of the KwaZulu-Natal Province, South Africa. Eniochobothrium acostae n. sp. is described on morphological and molecular grounds. The new species is placed within Eniochobothrium (viz., Eniochobothrium gracile Shipley and Hornell, 1906, Eniochobothrium qatarense Al Kawari, Saoud and Wanas, 1994, Eniochobothrium euaxos Jensen, 2005) by possessing key generic characteristics such as the absence of a vagina, expansion of the anterior region of the strobila forming a trough and presence of a thick-walled cirrus sac. Molecular phylogenetic analyses of the partial 28S rRNA and mtCOI genes confirm the generic characterisation as the newly proposed species groups together with other members of the genus. Eniochobothrium acostae n. sp. currently represents the largest described species of the genus; it possesses slightly fewer testes compared to most congeners, given that this feature has been provided in the original description (e.g., E. euaxos and E. qatarense ). The new species of Eniochobothrium is the fourth valid species described to date and the first species record from South African waters. Graphical abstract: Image 1 Highlights: A new lecanicephalidean cestode is formally described based on morphological and molecular grounds. Molecular phylogenies of ribosomal (partial 28S rRNA) and mitochondrial (mtCOI) genes are provided. Molecular phylogenetic analyses placed the new species within the genus Eniochobothrium and support its validity. The new species is the fourth species of Eniochobothrium known to date and the first recorded from Southern Africa. Given the number of unassessed rhinopterid hosts, several species of Eniochobothrium may await scientific discovery.